Uganda’s interaction with state reporting under the African Charter on Human and Peoples’ Rights and the African Charter on the Rights and Welfare of the Child - Magnus, Killander (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.